2018
DOI: 10.4236/health.2018.105047
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Blood Pressure Control Medicines Using Health and Medical Checkup Data in Japan: Alternative Methods for Randomized Controlled Trials

Abstract: Background: Many people take medicines to control high blood pressure (BP), or hypertension. Randomized clinical trials (RCT) are usually used for the evaluation of effects of medicines. However, RCT have some serious problems. Data and Methods: We evaluated the effects of BP medicines in Japan using a dataset containing 113,979 cases. We employed four statistical methods in the analysis. First, we simply compared the systolic blood pressure (SBP) of individuals with and without BP medicines. We then used a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…So, we cannot directly use Antihypertensive (taking antihypertensive drugs: 1; 0: otherwise) dummy because of the endogeneity problem (actually, if we directly use Antihypertensive in the regression equation, its estimate becomes + 4.80 mmHg). Nawata, Sekizawa and Kimura [34] suggested a method to take the expected value of the variable to solve the endogeneity problem, the following model evaluating the effect of Antihypertensive. (Model 1C):…”
Section: Analyses Of Factors Affecting Bp By Regression Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, we cannot directly use Antihypertensive (taking antihypertensive drugs: 1; 0: otherwise) dummy because of the endogeneity problem (actually, if we directly use Antihypertensive in the regression equation, its estimate becomes + 4.80 mmHg). Nawata, Sekizawa and Kimura [34] suggested a method to take the expected value of the variable to solve the endogeneity problem, the following model evaluating the effect of Antihypertensive. (Model 1C):…”
Section: Analyses Of Factors Affecting Bp By Regression Modelsmentioning
confidence: 99%
“…They found that the "white coat effect" was significant and suggested that the careful payments for upward errors of BP measurements were necessary. Nawata, Sekizawa and Kimura [34] pointed out the problems of the previous BP studies. They are: since the participants and doctors (or researchers) can easily know that the groups (treated or controlled) that they are belonging, the double blinded randomized clinical trials are impossible for the BP studies; trials with positive results are more likely to be published than those with negative or questionable results; researchers themselves might not have strong incentives to publish when the expected results are not obtained; in many studies sponsored by the pharmaceutical companies, biases toward the sponsor's products and conflicts of interest (CI) might occur; and practices are often terminated in the early stages for various reasons especially when expected results are not obtained (termination or endpoint biases).…”
Section: Introductionmentioning
confidence: 99%
“…However, questions have arisen about the results of previous studies, as pointed out by Nawata, Sekizawa, and Kimura [47]. Biases such as publication, conflict of interest, and termination (or endpoint) biases might exist in these studies.…”
Section: Reviews Of Previous Studiesmentioning
confidence: 99%
“…(1: with anamnesis; 0: otherwise) and Trend represents the time trend. For details, see Model 3 of Nawata, Sakizawa, and Kimura [47].…”
Section: Healthmentioning
confidence: 99%
“…The selection criteria of 61 studies used in the meta-analysis were not clarified. As pointed out by Nawata Sekizawa and Kimura [13], biases such as publication [14] [15] biases and conflicts of interest [16] might have existed, and the results could have been affected by such biases even if all studies were proper RCTs. Moreover, BP levels were strongly affected by various factors such as the age, gender, health conditions, and lifestyles of the individuals.…”
Section: Introductionmentioning
confidence: 99%